Differential infectivity by the oral route of Trypanosoma cruzi lineages derived from Y strain. - Cristian Cortez; Rafael M Martins; Renan M Alves; Richard C Silva; Luciana C Bilches; Silene Macedo; Vanessa D Atayde; Silvia Y Kawashita; Marcelo R S Briones; Nobuko Yoshida (PLoS Neglected Tropical Diseases)
Background Diversity of T. cruzi strains is a central problem in Chagas disease research because of its correlation with the wide range of clinical manifestations and the biogeographical parasite distribution. The role played by parasite microdiversity in Chagas disease epidemiology is still debatable. Also awaits clarification whether such diversity is associated with the outcome of oral T. cruzi infection, responsible for frequent outbreaks of acute Chagas disease. Methods and findings We addressed the impact of microdiversity in oral T. cruzi infection, by comparative analysis of two strains, Y30 and Y82, both derived from Y strain, a widely used experimental model. Network genealogies of four nuclear genes (SSU rDNA, actin, DHFR-TS, EF1α) revealed that Y30 is closely related to Discrete Typing Unit TcII while Y82 is more closely related to TcVI, a group containing hybrid strains. Nevertheless, excepting one A-G transition at position 1463, Y30 and Y82 SSU rDNAs were identical. Y82 strain, expressing the surface molecule gp82, infected mice orally more efficiently than Y30, which expresses a related gp30 molecule. Both molecules are involved in lysosome exocytosis-dependent host cell invasion, but exhibit differential gastric mucin-binding capacity, a property critical for parasite migration toward the gastric mucosal epithelium. Upon oral infection of mice, the number of Y30 and Y82 parasites in gastric epithelial cells differed widely. Conclusions We conclude that metacyclic forms of gp82-expressing Y82 strain, closely related to TcVI, are better adapted than Y30 strain (TcII) to traverse the stomach mucous layer and establish oral route infection. The efficiency to infect target cell is the same because gp82 and gp30 strains have similar invasion-promoting properties. Unknown is whether differences in Y30 and Y82 are natural parasite adaptations or a product of lab-induced evolution by differential selection along the 60 years elapsed since the Y strain isolation.